Thalidomide Embryopathy: An Enigmatic Challenge. (31st October 2013) - Vargesson, Neil
Abstract : Thalidomide remains one of the world's most notorious drugs due to the severe birth defects it induced in children between 1957 and 1962. Yet, to some this drug is a lifesaver, as it now enjoys renaissance in the treatment for a wide range of conditions including leprosy, multiple myeloma, Behcet's disease, and some cancers. However, thalidomide has also been linked to causing a new generation of thalidomide survivors in Brazil, where the drug is used to treat leprosy. Surprisingly how thalidomide causes birth defects and how it acts in the treatment of clinical conditions are still far from clear. In the past decade great strides in our understanding of the actions of the drug, as well as molecular targets, have been made. The purpose of this review is to look at the recent work carried out into understanding how thalidomide causes birth defects, it's molecular targets and the challenges that remain to be elucidated. These challenges include identifying clinically relevant but nonteratogenic forms of the drug, and the mechanisms underlying phocomelia and species specificity.